Power system economic and market operations - Zhong, Jin (CRC Press, Taylor & Francis Group, 2018)
Power system operation is one of the important issues in the power industry. The book aims to provide readers with the methods and algorithms to save the total cost in electricity generation and transmission. The book covers electricity pricing mechanisms, such as nodal pricing and zonal pricing, based on Security-Constrained ED (SCED) or SCUC. The operation of energy market and ancillary service market are also explored.